1993
DOI: 10.1113/jphysiol.1993.sp019787
|View full text |Cite
|
Sign up to set email alerts
|

Changes in crossbridge and non‐crossbridge energetics during moderate fatigue of frog muscle fibres.

Abstract: SUMMARY1. The effect of sarcomere length (SL) during a fatiguing series of isometric tetani of frog muscle fibres was investigated. Tetani at 2-3 ,um SL were more fatiguing than tetani at 3-2 ,sm SL, in that force declined twice as much and relaxation became much slower.2. In a second set of experiments the force and heat production were measured during a series of fatiguing tetani. Heat was separated into two components: (a) crossbridge heat which is dependent on filament overlap and interaction, and (b) non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 24 publications
1
22
1
Order By: Relevance
“…In all except the earliest (Allen et al 1989) of these studies a clear-cut reduction of the sensitivity was observed. The lack of any reduction in the earliest study is probably because the photoprotein aequorin was used to measure [Ca2+]i; its light emission is reduced by Mg2+, and we subsequently observed a marked increase in myoplasmic magnesium concentration ([Mg2+]i) in fatigue (Westerblad & Allen, 1992c Furthermore, fibres become more fatigue resistant when the number of energy-consuming cross-bridges is reduced by stimulating at long sarcomere lengths (Barclay, Curtin & Woledge, 1993). Finally, muscles fatigue more rapidly when the energy turnover is increased by active shortening during tetani (Cummins, Soomal & Curtin, 1989 Acidosis is one possible link between reduced Ca2' release and metabolism, since it has been shown that pH may affect the opening of isolated SR Ca2+ channels in lipid bilayers (Ma, Fill, Knudson, Campbell & Coronado, 1988).…”
Section: Reduction Of Maximum Isometric Forcementioning
confidence: 84%
“…In all except the earliest (Allen et al 1989) of these studies a clear-cut reduction of the sensitivity was observed. The lack of any reduction in the earliest study is probably because the photoprotein aequorin was used to measure [Ca2+]i; its light emission is reduced by Mg2+, and we subsequently observed a marked increase in myoplasmic magnesium concentration ([Mg2+]i) in fatigue (Westerblad & Allen, 1992c Furthermore, fibres become more fatigue resistant when the number of energy-consuming cross-bridges is reduced by stimulating at long sarcomere lengths (Barclay, Curtin & Woledge, 1993). Finally, muscles fatigue more rapidly when the energy turnover is increased by active shortening during tetani (Cummins, Soomal & Curtin, 1989 Acidosis is one possible link between reduced Ca2' release and metabolism, since it has been shown that pH may affect the opening of isolated SR Ca2+ channels in lipid bilayers (Ma, Fill, Knudson, Campbell & Coronado, 1988).…”
Section: Reduction Of Maximum Isometric Forcementioning
confidence: 84%
“…With respect to species, most earlier studies that estimated cross-bridge-dependent ATP consumption were performed on frog muscle, although studies on fish, chicken, mice, and rats have also been performed (2,7,25,31,41,42). Interestingly, recent studies (38) of fast-twitch (IIA/B and IIB) skinned human muscle fibers (at 20°C) demonstrated that cross bridges accounted for only 35-41% of total ATP consumption, whereas SR Ca 2ϩ pumping accounted for 52-55%.…”
Section: Discussionmentioning
confidence: 99%
“…From an energetic perspective, these findings may have relevance to the neural control of motor unit behaviour during contractions in which total muscle work or force maintenance is of greater importance than the rate of force rise. Minimizing the activation level or frequency of activation required to achieve a target force is energetically desirable (Barclay et al, 1993(Barclay et al, , 2008, as the metabolic cost of the contraction will be reduced accordingly.…”
Section: Discussionmentioning
confidence: 99%